Biological testing of chitosan‐collagen‐based porous scaffolds loaded with PLGA/Triamcinolone microspheres for ameliorating endoscopic dissection‐related stenosis in oesophagus. (4th February 2021) - Ni, Wenkai; Lin, Shengli; Bian, Saiyan; Xiao, Mingbing; Wang, Yongjun; Yang, Yumin; Lu, Cuihua; Zheng, Wenjie; Zhou, Pinghong
Abstract: Objectives: Endoscopic submucosal dissection (ESD), a preferential approach for early oesophageal neoplasms, inevitably results in oesophageal strictures in patients. Clinical use of glucocorticoids through submucosal injection is beneficial for inhibiting oesophageal stricture following injury; however, it also has limitations, such as dose loss and perforation. Hence, alternatives to glucocorticoid therapy should be developed. Methods: A novel porous composite scaffold, ChCo‐TAMS, composed of chitosan, collagen‐I and triamcinolone acetonide (TA) loaded into poly (lactic‐co‐glycolic) acid (PLGA) microspheres (TAMS), was successfully constructed and subjected to biological testing to ameliorate oesophageal ESD‐related stenosis. Results: The synthesized biomaterials displayed unique properties in inhibiting the activation of macrophages, chemokine‐mediated cell recruitment and fibrogenesis of fibroblasts. Further application of the scaffolds in the rat dermal defect and porcine oesophageal ESD model showed that these novel scaffolds played a robust role in inhibiting wound contracture and oesophageal ESD strictures. Conclusions: The developed composite scaffolds provide a promising clinical medical device for the prevention of post‐operative oesophageal stricture. Abstract : The composite porous scaffold ChCo‐TAMS containing chitosan, collagen and PLGA/Triamcinolone microspheres were synthesized and cross‐linked by genipin. In vitro assays demonstrated the inhibitory effects of the scaffolds upon macrophages activation and myofibroblasts transdifferentiation. The porcine model was established by performing circumferential ESD in oesophagus, and the post‐operative stricture was efficiently ameliorated by application of ChCo‐TAMS scaffolds.